Protection of Victims of Drug Abuse in the Perspective of Restorative Justice - Abdullah, Tegar Ishmat; Ramadhan, Mochammad Gilang; Ghoni, Ahmad Abdul; Waluyadi, Waluyadi; Fathurohman, Dadan Taufik (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study critically examines narcotics abuse through a restorative justice lens within the Indonesian legal system. Using a normative juridical method and qualitative analysis, data were collected through documentary research, with secondary sources as the primary reference. Case analysis of Decision No. 29/Pid.Sus/2024/PN Cbn highlights the dominance of retributive justice, which proves inadequate for addressing narcotics abuse. In contrast, Decision No. 272/Pid.Sus/2021/PN Bir demonstrates restorative justice through victim-centered rehabilitation and efficient legal procedures. The findings underscore the need to expand restorative approaches to better protect and rehabilitate victims, offering a more humane and effective alternative to punitive models.